Sistem Informasi Koperasi pada PT. Jadi Abadi Corak Biscuit - Hadiprasetyo, Darmawan; Rostianingsih, Silvia; Yulia, Yulia (Jurnal Infra, 2018)
In this current condition, cooperative PT Jadi Abadi Corak Biscuit still running all of their business processes manually. This condition causes profit from the minimarket still not included in the process of calculating the business revenue residu because of a lack of data integration between saving and loan of the cooperative and selling trasaction data of the minimarket. Moreover, the employee on duty is also having problem in doing stock opname and making the reports needed becuase they first have to adjust the data of purhcasing and selling mnually. Another problem is also found when calculating the business revenue residu, this process will waste a lot of time because they first have to gather all the reports in a year, make the profit and loss report, then they have to input all data of the member one by one into excel.The final result of making this cooperative information system is user of this system can see the remaining stock of goods, calculate the business revenue residu, and retrieves all the reports needed in managing the cooperative. From the questionnaire results, scores are given 100% on the assessment of the interface of the application, 100% in ratings features both selling and purchasing features, and 100% on an overall assessment of the problem either.